Capturing the value of unstructured data in procurement : Case study on supplier contracts - Mäkinen, Aleksi (My University, 2021)
Data is becoming more and more important to organizations. Many studies suggest that unstructured data, which cannot be managed traditionally, would be the new frontier of value-adding data for the organizations and contribute over 80% of the data organizations have available in their operations. This alarms us to turn our focus on this phenomenon and study what type of data the unstructured data is, how organizations should manage it, and why they should start investing into it. The research will study how organizations’ procurement function, a function responsible for acquiring the services and goods for business operation, should approach unstructured textual data and include this data into their business analytical processes and what is the expected value of unstructured textual data in procurement analytics. The research presents a thorough literature review on the topic. Literature covers the main principles of unstructured textual data, key factors when assessing the approach and capability to utilize the data, and which type of value procurement should seek from the unstructured textual data. As part of the theoretical review, we will compose a theoretical framework, which is used to assess the main research questions: How should procurement organizations approach unstructured textual data? What is the expected value of the unstructured textual data in procurement? The research also includes a case study with two procurement organizations, which assess their approach and the value of unstructured textual data in their organization. The specific use case of unstructured textual data these organizations evaluate is supplier-related documents, such as supplier contracts. The findings from the case study will be reflected in the theoretical framework of the research, providing a practical point of view to the research results and conclusions. We consider the research framework and results to provide valuable information for procurement organizations which consider including unstructured textual data from the supplier-related documents into their analytical processes.
Keywords: procurement, procurement analytics, unstructured data, supplier contracts